2011
DOI: 10.1007/s11434-011-4914-0
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of rat calvarial defects by poly(lactide-co-glycolide)/hydroxyapatite scaffolds loaded with bone mesenchymal stem cells and DNA complexes

Abstract: A composite construct comprising of a bone mesenchymal stem cell (BMSC) sheet, plasmid DNA, encoding human bone morphogenic protein-2 (hBMP-2), and poly(lactide-co-glycolide)/hydroxyapatite (PLGA/HA) sponge was designed and employed in the restoration of rat calvarial defects. To improve gene transfection efficiency, a cationic chitosan derivative, N,N,N,-trimethyl chitosan chloride (TMC), was employed as the vector. The TMC/DNA complexes had a transfection efficiency of 13% in rat BMSCs, resulting in heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Setting the joint site as an example, this site exhibits less host responses to implant, because more body fluids and faster fluid exchange are helpful for removing the acidic degradation products effectively. In fact, many positive results of tissue repairing using PLA or PLGA porous scaffolds have been reported [27][28][29][30]48,49]. Our group has recently revealed that the body fluid exchanged faster than we initially supposed, even at the subcutaneous site, for a block copolymer hydrogel composed of PLGA-PEG-PLGA with initial pH 4 became neutral just ten hours after a subcutaneous injection into SD rats [50].…”
Section: Is There Any Significant Difference Of Cytotoxicity Between mentioning
confidence: 93%
See 1 more Smart Citation
“…Setting the joint site as an example, this site exhibits less host responses to implant, because more body fluids and faster fluid exchange are helpful for removing the acidic degradation products effectively. In fact, many positive results of tissue repairing using PLA or PLGA porous scaffolds have been reported [27][28][29][30]48,49]. Our group has recently revealed that the body fluid exchanged faster than we initially supposed, even at the subcutaneous site, for a block copolymer hydrogel composed of PLGA-PEG-PLGA with initial pH 4 became neutral just ten hours after a subcutaneous injection into SD rats [50].…”
Section: Is There Any Significant Difference Of Cytotoxicity Between mentioning
confidence: 93%
“…That is why polyesters have been studied for a long time [14][15][16][17][18][19][20]. A lot of efforts have been done on improving the biocompatibility of the polyester porous scaffolds [21][22][23][24][25][26][27][28], and examinations of their medical applications [27][28][29][30][31][32][33].…”
mentioning
confidence: 99%
“…In one study, PEI25 was beneficial when pDNA was delivered in scaffolds in a cranial defect site . Other studies with sustained release formulations or a carrier functional in vitro ( N,N,N ‐trimethyl chitosan) did not result in improved bone formation in a similar intracranial site. It remains to be seen whether the scaffold effects (chemical composition, physical architecture controlling cell invasion, degradation products, etc.)…”
Section: Pharmacokinetics and Pharmacodynamics Of Gene Deliverymentioning
confidence: 99%
“…In our previous study, a hybrid scaffold of fibrin gel and PLGA sponge was proposed to act as a biomimetic tissue platform for cartilage regeneration . The porous sponges own the ease for processing and can supply comparable mechanical strength with the cartilage tissue. However, the sponge alone is not competent to provide inductive signals for cell differentiation. The hydrogels are favorable for cell survival, proliferation, and differentiation, yet they have a rather weak mechanical strength. , The hybrids composed of sponges and hydrogels may overcome the disadvantages of each type of scaffold.…”
Section: Introductionmentioning
confidence: 99%